STEREOTYPES AND THEIR IMPACT ON A PERSON'S PERSONAL DEVELOPMENT - Balous, Lulu (E-Journal VFU, 2026)
Stereotypes are deeply ingrained in societies and influence individual development in profound ways. While some stereotypes serve as cognitive shortcuts, others can limit opportunities, shape self-perception, and hinder personal growth. This paper explores the psychological, social, and professional impact of stereotypes on personal development, using academic sources to analyze their consequences and potential solutions.
Keywords: Stereotypes; cognitive shortcuts; individual development; psychological impact; social influence; professional impact; self-perception; consequences